Literature Review on Needs of Upper Limb Prosthesis Users - Cordella, Francesca; Ciancio, Anna Lisa; Sacchetti, Rinaldo; Davalli, Angelo; Cutti, Andrea Giovanni; Guglielmelli, Eugenio; Zollo, Loredana (Frontiers in Neuroscience, 2016)
The loss of one hand can significantly affect the level of autonomy and the capability of performing daily living, working and social activities. The current prosthetic solutions contribute in a poor way to overcome these problems due to the limitations of the interfaces adopted for controlling the prosthesis and to the absence of force or tactile feedback which limit the hand grasp capabilities. In order to provide indications for further developments in the prosthetic field to increase user satisfaction rates and therefore to reduce device abandonment, this paper reports a literature review on needs analysis of upper limb prosthesis users, by pointing out the critical aspects of the prosthetic solutions in terms of users satisfaction and activities of daily living they would like to perform with the prosthetic device. A list of requirements for upper limb prostheses is proposed, grounded on the performed analysis on user needs. The defined list of requirements for the prosthetic system aims to provide (i) some guidelines for improving the level of acceptability and usefulness of the prosthesis, by accounting for hand functional and technical aspects; (ii) a possible functional scheme of a PNS-based prosthetic system able to satisfy the emerged user wishes; (iii) some hints for improving the quality of the methods (such as questionnaires) adopted for understanding the user satisfaction with their prosthesis.